Analysis of The Influence of Bank Financial Performance on The Profitability of Conventional Rural Banks in Lampung Province - Saputri, Intan; Herlina Sitorus, Nurbetty (Lafadz Jaya Publisher, 2024)
Profitability is one of the most important elements in the success and survival of banking. Good profitability will benefit the economy as a whole which can provide more loans to small and micro businesses and support local economic growth, namely through Rural Banks. The purpose of this study was to determine the effect of CAR, NPL, LDR, BOPO, and KAP on the profitability of conventional Rural Banks in Lampung province for the period 2016-2023. The research method used in this research is quantitative research method. The data analysis technique uses panel data regression. The results showed that CAR and LDR had a positive and significant effect on ROA, while NPL, BOPO, and KAP had a negative and significant effect on ROA. Simultaneously CAR, NPL, LDR, BOPO, and KAP together have a significant effect on ROA.